Delamination detection in composite laminate plates using 2D wavelet analysis of modal frequency surface. (15th January 2017) - Yang, Chen; Oyadiji, S. Olutunde
Highlights: Novel damage detection approach using modal frequency surface (MFS) is presented. MFS wavelet coefficients developed as new indicator for damage localisation. MFS wavelet coefficients characterise both near and far surface delaminations. Damage indicator highly sensitive to near surface delamination even under noise. Location, severity and shape of delaminations identified by damage indicator. Abstract: A novel damage detection approach, using modal frequency surface (MFS), is presented. By attaching a point mass at different locations, the MFS is generated. Delamination causes a discontinuity in the MFS due to reduction of local stiffness. Finite element method is employed to simulate the modal frequency data. The frequency deviations show a quasi-exponential decrease as the delamination depth increases. MFS wavelet coefficient is computed and its magnitude under different random noise levels is discussed. It is shown that the MFS wavelet coefficient can characterise the location and shape of both near and far surface delaminations in laminated composite plates.